2019
DOI: 10.1074/jbc.ra118.006549
|View full text |Cite
|
Sign up to set email alerts
|

A polybasic motif in alternatively spliced KChIP2 isoforms prevents Ca2+ regulation of Kv4 channels

Abstract: Edited by Roger J. ColbranThe Kv4 family of A-type voltage-gated K ؉ channels regulates the excitability in hippocampal pyramidal neuron dendrites and are key determinants of dendritic integration, spike timing-dependent plasticity, long-term potentiation, and learning. Kv4.2 channel expression is down-regulated following hippocampal seizures and in epilepsy, suggesting A-type currents as therapeutic targets. In addition to pore-forming Kv4 subunits, modulatory auxiliary subunits called K ؉ channel-interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 55 publications
(76 reference statements)
2
15
0
Order By: Relevance
“…Because all current parameters were measured within a time range between tens of seconds and a few minutes after establishing the whole-cell configuration, the observed Ca 21 effects can be classified as acute. Acute Ca 21 effects on the surface expression of Kv4.2/KChIP complexes in the whole-cell patch-clamp configuration have been studied previously by Murphy and Hoffman (37), who found increased Kv4.2 current densities with elevated Ca 21 in the pipette solution for certain KChIP isoforms including the KChIP3a splice variant used in the present study. The authors suggested a post-ER/Golgi pool of Kv4/KChIP channel complexes recruited to the plasma membrane in a Ca 21 -dependent manner.…”
Section: Mode Of Cln3 Action On A-type Potassium Channelssupporting
confidence: 57%
“…Because all current parameters were measured within a time range between tens of seconds and a few minutes after establishing the whole-cell configuration, the observed Ca 21 effects can be classified as acute. Acute Ca 21 effects on the surface expression of Kv4.2/KChIP complexes in the whole-cell patch-clamp configuration have been studied previously by Murphy and Hoffman (37), who found increased Kv4.2 current densities with elevated Ca 21 in the pipette solution for certain KChIP isoforms including the KChIP3a splice variant used in the present study. The authors suggested a post-ER/Golgi pool of Kv4/KChIP channel complexes recruited to the plasma membrane in a Ca 21 -dependent manner.…”
Section: Mode Of Cln3 Action On A-type Potassium Channelssupporting
confidence: 57%
“…We and others have reported that Kv4.x current density is increased when intracellular free Ca 2+ is increased to the μM range (42, 71). Nanoscale binding of Cav2.3 and Kv4.2 suggests that Cav2.3 could act as a local μM-source of free Ca 2+ .…”
Section: Resultsmentioning
confidence: 85%
“…Variant KChIPs have been categorized based on the tendency for the N-terminus to mediate membrane interactions (33). A subset of “cytoplasmic” KChIP isoforms confer Ca 2+ regulation onto Kv4.2 channel complexes, N- myristoylated isoforms do not, and reversibly palmitoylated isoforms have mixed Ca 2+ sensitivity (42). Members of a fourth transmembrane class of KChIPs retain Kv4.2 complexes within the ER and reduce Kv4.2 surface expression when compared with other KChIP isoforms (108).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations